Policy for Setting Maximum Limits for Individual Ownership of Non-Agricultural Property Rights Based on Justice Values - Rachmandhani, Afrizal Yannuar (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This research aims to determine and analyze the application of the maximum limit of individual ownership of non-agricultural land ownership rights in Subang Regency, based on the value of justice, and to find out and analyze the monitoring efforts carried out by the National Land Agency regarding the maximum limit of non-agricultural land ownership rights in Subang Regency National Land Agency Office. The research approach method used in the thesis is a sociological juridical approach. Specifications This research uses analytical descriptive research. The type and data used in this research are primary data which includes the 1945 Constitution; Act No. 5 of 1960 concerning Basic Regulations on Agrarian Principles; Civil Code Law. As well as secondary data containing books and other supporting documents. Data collection using interview techniques and study of documents or library materials. The data analysis method used in analyzing data is data triangulation. Sugiyono stated that data triangulation is defined as a data collection technique and existing data sources. Keywords: Justice; Limits; Maximum; Policies; Values.